FRI0097 Baseline Serum 14-3-3 ETA Independently Predicts Clinically Important Improvements in HAQ-DI in Patients with Rheumatoid Arthritis Treated with Tocilizumab. (15th July 2016) - Hirata, S.; Hanami, K.; Marotta, A.; Tanaka, Y.
Abstract : Background: Serum 14–3-3η is a mechanistic marker that is involved in the pathogenesis of RA and is a direct and potent up-regulator of IL-6. 1 We previously reported that baseline 14–3-3η levels were significantly lower in a cohort of 49 established RA patients who achieved better clinical outcomes when treated with Tocilizumab. 2 Recently there has been increased interest in assessing therapy response using alternative measures to DAS that are independent of CRP, including patient reported outcomes such as HAQ-DI. Objectives: The aim of this study was to evaluate whether baseline measurement of 14–3-3η was associated with and independently predicted clinical response, in a cohort of 106 RA patients treated with tocilizumab. Methods: Serum 14–3-3η levels were measured in a cohort of 106 Japanese patients prior to the initiation of tocilizumab therapy (BL). 14–3-3η positivity was defined by the diagnostic cut-off of ≥0.19 ng/ml, and 2 and 4 times that, at 0.40 and 0.80 ng/ml, respectively. Patients were sub-grouped according to changes in HAQ-DI based on the minimal clinically important difference (MCID) of ≥0.22, ≥0.31, and ≥0.49. Group differences were assessed by Mann-Whitney U-test. ROC curve analysis was performed to identify the optimal 14–3-3η cut-point for a ΔHAQ-DI ≥0.49. Uni- and multi-variable analysis controlling for baseline HAQ-DI was used to assess 14–3-3η's independence of other clinical/serological variables at informing patient reported outcomes. Results: At baseline, 75 (71%) of the 106 patients were 14–3-3η positive. At year 1, 70 (66%), 58 (55%) and 52 (40%) of the 106 patients achieved changes in HAQ-DI of ≥0.22, ≥0.31, and ≥0.49, respectively. Baseline HAQ-DI values were significantly higher in those patients that achieved a Δ HAQ-DI ≥0.22 when compared with those that did not; p=0.009. The HAQ-DI values were also significantly higher at the two other HAQ-DI cut-points (≥0.31, and ≥0.49), p<0.0001. As shown in the Figure, serum 14–3-3η levels were significantly lower in patients that achieved HAQ-DI MCID of >0.31 and >0.49. In patients who achieved a DHAQ-DI ≥0.49, ROC analysis returned the best cut-off of ≤0.18 ng/ml yielding a specificity of 83.3% (95%CI: 70.7–92.1) and sensitivity of 42.3% (95%CI: 28.7–56.8), LR =2.5. By univariate analysis, all three 14–3-3η cut-points were significantly associated with better clinical outcomes. Multi-variable modeling controlling for BL HAQ-DI indicated that lower levels of 14–3-3η, age and disease duration, but not CRP, were independent predictors of achieving the HAQ-DI MCID outcomes. Conclusions: Lower serum 14–3-3η levels prior to the initiation of therapy are associated with and independently predict better patient reported outcomes in patients treated with tocilizumab. The predictive capacity of 14–3-3η at informing therapy response to anti-IL-6 therapy should be investigated across all anti-IL-6 compounds. References: Arthritis Rheum. 2014; 66 (Suppl 11):1975. Arthritis Res Ther. 2015; 17:280. Disclosure of Interest: S. Hirata Speakers bureau: AbbVie, Eisai, Bristol Meyers Squibb, K. Hanami: None declared, A. Marotta Employee of: Augurex Life Sciences Corp., (Co-inventor of 14–3-3η), Y. Tanaka Grant/research support from: Mitsubishi-Tanabe, Chugai, MSD, Astellas, Novartis, Speakers bureau: Abbvie, Chugai, Astellas, Takeda, Santen, Mitsubishi-Tanabe, Pfizer, Janssen, Eisai, Daiichi-Sankyo, UCB, GlaxoSmithKline, Bristol-Myers